Особливості ІЛ-2-залежної ланки імунітету у пацієнтів з захворюванням нирок (пієло- та гломерулонефрит) - Гайсенюк, Ф.З.; Дріянська, В.Є.; Кривенко, Є.О.; Петрина, О.П.; Драннік, Г.М.; Порошина, Т.В.; Калініна, Н.А. (Таврический медико-биологический вестник, 2012)
Исследованы особенности продукции ИЛ-2 и числа ИЛ-2Р+-клеток у больных ПН и ГН. Показано,
что для пациентов обеих групп характерно повышение уровня ИЛ-2Р+-лимфоцитов, а для больных с
ПН – повышение спонтанной продукции ИЛ-2 при снижении митоген-индуцированной. Выявлены
асоциативные связи высоких показателей ИЛ-2-зависимого звена иммунитета и HLA-фенотипа (HLA-
А10, DR2) при ХГН, НС. The peculiarities of the IL-2 production and the number of IL-2P+ cells in the PN and GN patients were
analyzed. It was shown that the patients of both groups had the specific increase in the level of IL-2P+
lymphocytes but the PN patients had the increased spontaneous IL-2 production with the decrease in mytogeninduced
one. The associated relations between the high levels of IL-2-dependent immunity link and HLAphenotype
(HLA-А10, DR2) in CGN and NS were found.